ASSESSING THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES ON EMPLOYEE PERFORMANCE IN THE HEALTH SECTOR IN MACHAKOS COUNTY, KENYA - MUTUA, JEMMY M. (International Journal of Economics, Commerce and Management, 2017)
The study sought to determine the influence of Human resource management practices on employee performance in the health sector in Kenya; study of selected hospitals in Machakos Town .The specific objectives were; to investigate the influence of manpower planning on the performance of employee on selected hospitals in Machakos Town; to determine the influence of recruitment and selection on the performance of employees on selected hospitals in Machakos Town; to establish the influence of training and development on the performance of employee on selected hospital in Machakos Town ; and to examine the influence of reward and compensation on the performance of employees on selected hospitals in Machakos Town .The study adopted a mixed research design and the targeted employees grouped in 5 strata consisting top management, doctors, pharmacists, clinical officers, and nurses. Stratified random sampling was used to select a total of 251 respondents from a population of 709 from the various strata’s identified. Self- administered questionnaires were used to collect data. The study used multivariable linear regression using SPSS. The study asserts that manpower planning recruitment and selection, training and development, reward and compensation had significant positive relationship with employee performance. The study concludes that manpower planning, recruitment and selection, training and development, reward and compensation is positively related to employee performance. The study recommends that the management of the hospitals should incorporate manpower planning in their organization. The management should recruit and select employees fairly without any discrimination. The organization should arrange for training and development activities for their employees. The management should reward their employees for work well done.
Keywords: Human Resource